Peran zink terhadap sistem imun anak - Nova Yulia Rita; Rita Evalina; Lily Irsa (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
The human body consists of elements of macro and micro elements. One of the many trace elements are zinc beside iron. It has biologic immunostimulatory, which is a mineral that can stimulate immune function, where these nutrients play an important role in keeping the immune system with the enzyme works as a catalyst, facilitating the formation of proteins and gene expression regulation. Zinc plays a role in the catalytic activity karbonase anhydrase, and is a component of over 100 enzymes of six classes of enzymes. Bioinformatics estimates that about 10% of the body protein binds to zinc. Keywords : zinc; imun system; essensial mineral